SHELL FROM PALM OIL TREE PREPARED FOR VALUABLE PRODUCTS (CARBON MOLECULAR SIEVE AND CARBON ADSORBENT) - Herawan, Safarudin Gazali; Mohamad, Imran Syakir; Mohd Husin, Mohd Haizal; Yusof, Ahmad Anas; Mat Tokit, Ernie (2004)
Shell from palm oil tree or oil palm shell is an gricultural waste material found abundantly in Malaysia. Since the characteristics of oil palm shell was found suitable for preparing activated carbon, this material also has the potential to be prepared into useful and valuable product. This research, the concern is to make use of oil palm shell to prepare carbon molecular sieve (CMS) for separation of methane from carbon dioxide and carbon adsorbent, which applied for LPG gas storage. Both samples were prepared at a laboratory scale fixed-bed reactor, which is blanketed by a vertical furnace where pyrolysis took place. Nitrogen gas was used to obtain an inert atmosphere in the reactor. A suction blower was used to remove volatile matter as well as other gases during carbonization process. The samples were prepared in the different conditions to meet the application. CO2 activation also was used to investigate the effect of it in the sample. This research work will attempt to find a suitable solution to solve the environmental problems by utilizing the waste materials and to look into the industrial aspect of separation and adsorption process.